Still evangelical? : insiders reconsider political, social and theological meaning - Labberton, Mark, 1953- (Downers Grove, IL : InterVarsity Press, 2018)
Evangelicalism in America has cracked, split on the shoals of the 2016 presidential election and its aftermath, leaving many wondering if they want to be in or out of the evangelical tribe. The contentiousness brought to the fore surrounds what it means to affirm and demonstrate evangelical Christian faith amidst the messy and polarized realities gripping our country and world. Who or what is defining the evangelical social and political vision? Is it the gospel or is it culture? For a movement that has been about the primacy of Christian faith, this is a crisis. This collection of essays was gathered by Mark Labberton, president of Fuller Theological Seminary, who provides an introduction to the volume. What follows is a diverse and provocative set of perspectives and reflections from evangelical insiders who wrestle with their responses to the question of what it means to be evangelical in light of their convictions. --
Introduction. Still evangelical? / Mark Labberton -- Will evangelicalism surrender? / Lisa Sharon Harper -- Why I am an evangelical / Karen Swallow Prior -- Recapturing evangelical identity and mission / Mark Young -- Immigration and the Latina/o community / Robert Chao Romero -- Evangelical futures / Soong-Chan Rah -- Theology and orthopraxis in global evangelicalism / Allen Yeh -- Remaining to reform / Sandra Maria Van Opstal -- Looking for unity in all the wrong places / Mark Galli -- Evangelicalism must be born again / Shane Claiborne -- The importance of listening in today's evangelicalism / Jim Daly -- Hope for the next generation / Tom Lin.
Includes bibliographical references.
Keywords: Evangelicalism; Christianity and culture